Lipidomic analysis of diatoms cultivated with silica nanoparticles - Řezanka, Tomáš; Řezanka, Michal; Mezricky, Dana; Vítová, Milada (Phytochemistry, 2020)
Polar lipids from the diatoms Diadesmis gallica and Navicula atomus were separated and their structures were determined using high resolution tandem MS HILIC-LC/ESI. This method allowed us to identify 34 classes of lipids, each containing dozens of molecular species, including regioisomers. The largest differences were found in two sulfur-containing lipids, sulfoquinovosyldiacylglycerol and phosphatidylsulfocholine caused probably by the remodeling of lipid species. These diatoms have been found to use several mechanisms to resolve growth in extreme environments, i.e. silica starvation. The presence of insoluble nano-SiO2 leads to the replacement of cellular phospholipids with sulfolipids. Regioisomer ratios also vary depending on the concentration of nano-SiO2 in the culture medium, i.e. the biosynthesis of polar lipids via the prokaryotic (plastidial) and/or eukaryotic (explastidial) pathways. Complex analyses of polar lipids using high resolution HILIC-LC/ESI-tandem, as used for diatoms, can also be used for other photosynthetic microorganisms.
Keywords: rozsivky; Diadesmis gallica; oxid křemičitý; Phosphatidylsulfocholine; Silicon Dioxide; hmotnostní spektrometrie s elektrosprejovou ionizací; Diatoms; Lipidomics; Liquid chromatography-electrospray mass spectrometry; Naviculaceae; Silica nanoparticles; lipidomika; Nanoparticles; Diadesmidaceae; Fatty acids; Spectrometry, Mass, Electrospray Ionization; Navicula atomus; nanočástice